SDM PENDIDIKAN DASAR YANG UNGGUL: INTEGRASI PENELITIAN, TEORI, DAN KEPATUHAN YURIDIS - Dahlia, Ida; Puspito Rini, Puput; Suherman, Suherman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This article examines the importance of integrating empirical research, educational theory, and juridical compliance in the primary education sector's human resource (HR) development. This review investigates how combining these three elements can strengthen teaching and management practices in primary education, focusing on improving the quality of education and adherence to applicable juridical standards. Through extensive literature analysis, this article evaluates the effects of this integrated approach in the context of actual educational practice, exposing the benefits and challenges that arise. Key findings suggest that effective integration enables evidence-based policy development, enhances teachers' professional skills, and supports implementing innovative practices that comply with education regulations. This article emphasizes the importance of the ongoing commitment of all stakeholders in education to implement and sustain this integration, suggesting that long-term success in primary education depends mainly on the ability to adapt and apply research findings, educational theory, and juridical compliance harmoniously.